∫ 1 2 [ ( 1 + a ln ( x ) ) x x a + a − 1 ] d x = 1 5 , a = ?
Note: a is a constant.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
∫ 1 2 ( 1 + a l n ( x ) ) x x a + a − 1
Substitute x a = u
a 1 ∗ ∫ 1 2 a ( 1 + l n ( u ) ) u a u
Well, here I used the fact that d x d x a x = x a x a ( l n ( x ) + 1 ) . Well, everyone might want to consider that because we know on being 'derivated', it will give back itself "plus" "something".
Io, we have a very nice integral answer -
u a u , from 1 to 2 a .
2 2 a − 1 = 1 5
Hence, a = 2
Really, what a nice integral!
Problem Loading...
Note Loading...
Set Loading...
Deriving the function f ( x ) = x x a = e ( ln x ) x a , you get
f ′ ( x ) = e ( ln x ) x a ( x 1 x a + ( ln x ) a x a − 1 ) = x x a x a − 1 ( 1 + a ln x ) = x ( x a + a − 1 ) ( 1 + a ln x )
You can now see that the function f ′ ( x ) is under the integral, so we can use calculus fundamental theorem to say
∫ 1 2 x ( x a + a - 1 ) ( 1 + a ln x ) = x x a ∣ ∣ ∣ 1 2 = 2 2 a − 1
Since the function y = 2 2 x is an increasing function, the equation 2 2 a − 1 = 1 5 has only the solution a = 2 .